Karakteristik Fermentasi Rumen Domba Secara In Vitro dengan Pemberian Maggot Black Soldier Fly yang Dipelihara dengan Ampas Teh dan Ampas Sagu: Characteristics of In-Vitro Sheep Rumen Fermentation of Black Soldier Fly Maggot Reared on Tea Waste and Sago Pulp - Dilla Mareistia Fassah; Nella Nurhazizah; Dewi Apri Astuti; Lilis Khotijah (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2022)
The objective of this study was to evaluate the chemical composition of Black Soldier Fly (BSF) maggot grown in tea waste or sago pulp medium and their effects on fermentability and digestibility (in vitro). A randomized block design with 3 dietary treatments and 4 groups of rumen source from different sheep was used in this study. Dietary treatments consisted of P1 = soybean meal protein ration, P2 = BSF maggot meal protein ration grown in tea waste, P3 = BSF maggot meal protein ration grown in sago pulp. The data were analysed using ANOVA followed by Duncan's test. The results show that the NH3 concentration was higher (p<0.05) in treatment containing maggot meal protein grown in tea waste than others. However, each treatment did not have a significant effect on pH, total VFA, dry matter digestibility and organic matter digestibility in vitro. In conclusion, BSF maggot grown in tea waste and sago pulp media can replace soybean meal as a protein source in the ration without any negative effects on in vitro fermentability and digestibility. Key words: black soldier fly, digestibility, fermentability, in vitro, rumen microbes